Component reduced current-mode full-wave rectifier circuits using single active component - Sagbas, Mehmet; Minaei, Shahram; Ayten, Umut Engin (INST ENGINEERING TECHNOLOGY-IET, 2016)
This study presents the design of current-mode full-wave rectifier circuits using single active component. The first proposed circuit uses only one operational transconductance amplifier (OTA), two diodes and two resistors. Its current gain can be electronically controlled using the transconductance gain of the OTA. The second proposed circuit uses only one differential voltage current conveyor (DVCC), two diodes and three resistors. Using the complementary metal-oxide semiconductor structure of both OTA and DVCC, the behaviours of the proposed structures have been verified by HSPICE simulations. In addition, both of the proposed circuits are tested practically using commercially available components, such as AD844 and LM13700.
Keywords: CURRENT CONVEYOR; PRECISION RECTIFICATION; VOLTAGE CONVEYORS; Engineering